2015
DOI: 10.1016/j.ijnurstu.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Screening and brief intervention delivery in the workplace to reduce alcohol-related harm: A pilot randomized controlled trial

Abstract: Aims: To explore the feasibility and cost effectiveness of screening and delivery of a brief intervention for hazardous drinking employees.Methods: A pilot randomised controlled trial of a brief intervention delivered by an Occupational Health nurse versus no delivery of brief intervention (control group) conducted in a Local Authority Council (LCA) in the United Kingdom. Changes in quality of life and economic indicators were measured by the EQ-5D.Results: 627 employees were screened of whom 163 (26.01%) fulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 33 publications
0
41
0
1
Order By: Relevance
“…A similar result was found in another study that, although did not mention a significant effect on alcohol consumption, reported a considerable reduction in the consumption frequency of the examined workers. 9 The question about the need to drink alcohol in the morning after having drunk a lot in the night before showed more significant results, given that the mean was equal to zero, that is, no worker mentioned to have this desire in the evaluation carried out three months after the BI. Studies found that consumption reduction after BIs was higher among people who had a risky consumption, hazardous consumption, or probable dependence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A similar result was found in another study that, although did not mention a significant effect on alcohol consumption, reported a considerable reduction in the consumption frequency of the examined workers. 9 The question about the need to drink alcohol in the morning after having drunk a lot in the night before showed more significant results, given that the mean was equal to zero, that is, no worker mentioned to have this desire in the evaluation carried out three months after the BI. Studies found that consumption reduction after BIs was higher among people who had a risky consumption, hazardous consumption, or probable dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The authors confirmed the viability of alcohol consumption screening and the effect on the reduction of the consumption by workers, corroborating some international studies carried out in worker health services of some companies. 7,9,[16][17] The workers that had a high risk of alcohol consumption reduced their excessive consumption, although they did not consider themselves as people who drink too much. Some studies show that 9/12 the decrease is higher in the three first months after the BI and tends to diminish over time, which emphasizes the need for worker health teams to monitor the participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies conducted at large companies and tested the efficacy of web based as well as face to face alcohol brief intervention [37][38][39][40]. Although less attention has been given to workplace as an arena for brief alcohol interventions due to heterogeneous barriers on its acceptance and potential effectiveness, evidence on its efficacy is growing [41,42] even from developing countries [43,44].…”
Section: Alcohol Brief Interventions In Workplace Settingsmentioning
confidence: 99%